Legitimidade da representação em conselhos de saúde : o caso do Conselho Municipal de Saúde de Vitória-ES - Sipioni, Marcelo Eliseu (2009)
The Public Policies Management Councils emerged on the Brazilian scene with the 1988 Federal Constitution, which enshrined the social participation principle in various constitutional provisions. Thus, the Brazilian legal system has set up an hybrid institutional architecture, in that it focuses on the combination of representation and social participation. The latter, provided via management councils, put into play a new theoretical problem whose focus is the relationship between representation and participation, because the theoretical debate tends to focus on representation (representative democracy) or participation (Participatory Democracy). In this debate, both appear as separate constitutive forms of different models of democracy. However, this dualization has overlooked an essential dimension in terms of participatory experiences with regard to how to structure the processes of representation in participatory spaces. The premise of this study, therefore, is that both ideas are complementary, not antithetical. From there, we seek to ascertain in the Municipal Health Council of Vitoria, Espirito Santo, how the relationship between representatives and represented occur through a process that is being considered, by the recent literature, as determining the legitimacy of this relationship: authorization and accountability. This is a qualitative research, featured as a case study where we used the technique of the Collective Subject’s Discourse – DSC – to organize the interviews in order to map, therefore, some political networks built within the Council, in order to show how legitimate is the representation relationship between civil society’s counselors and their respective entities. The results show some limits to representation in the studied Council with a clear distance between the representative and its political base. However, some progress could also be observed. Some statements showed an attempt by some subjects in order to catch up with their entities and these, in turn, charge their representatives the return required to occur the legitimate representation. These findings do not suggest anything more than the obvious need to undertake further studies on this topic.